Radar Sounding Confirms a Hydrologically Active Deep-Water Subglacial Lake in East Antarctica - Li, Yan; Lu, Yang; Siegert, Martin J. (Frontiers in Earth Science, 2020)
Lake CookE2, upstream of Cook Glacier in East Antarctica is an ‘active’ subglacial lake, which experiences episodic discharge and recharge of basal water. Although around 130 active lakes are known to exist, the majority are not able to be identified by radar sounding techniques, suggesting they are ephemeral and/or distributed stores of small amounts of water rather than permanent significant singular features. Airborne ice-sounding radar data from Lake CookE2, a known ‘active’ subglacial lake, reveal a bright and flat ice-bed interface, providing clear evidence of deep (>10 m) water surrounded by elevated topography, however. The data reveal the lake area is ~46 km2; 3 times less than a previous estimated (145 km2) from ICESat surface altimetry, indicating a possible bias in identifying subglacial lake area from surface depressions. Using time-series altimetry from ICESat, Cryosat-2 data, and the Reference Elevation Model of Antarctica, we re-estimate the lake discharged ~2.93 km3 of water (or ~63.8 m in lake level) between February 2006 and January 2011. Subsequently, the ice surface over the lake rose steadily and experienced a mean uplift of ~11 m between January 2011 and November 2016, indicating continuous recharge with total volume increase of ~0.51 km3. The lake is recharging at a rate of ~1.33 m/year, which means it will take another ~39 years to reach the lake level that triggered the previous discharge.